A escola Normal em Canguçu: itinerário da primeira turma de formandas (1965-1970) - Zaneti, Patrícia Silveira (2012)
The study has as focus the first group of the Normal Course of Canguçu, of the Franciscan School Ours Mrs. Aparecida tends as temporary cutting the period from 1965 to 1970, context in that happens the implantation of the course and graduation of the group. We started by a contextualization of the municipality of Canguçu presenting the educational reality in the period of analysis. Following by a retrospect of Franciscan institutions until the arrival of the order in the city, emphasizing the conditions in which the installation of the normal course. We who were the students, as well as the first professionals who took part in this training. We analyzed the role of the enrolment of students, the curriculum, the rules, practice intra and walls, passing by the probationary and reaching to the day of graduation. The class was a milestone in the education of the municipality and the region, since that was the first teacher-training school in the city, while maintaining its activities until today, following ideals Franciscans. For this work we use documentary research and oral history in an attempt to presentificar the past absent, trying to weave the nexus, crossing the wires of various sources, up the history of education that we have now. Therefore the research is an important milestone in the education of Canguçu, being that this first class vanishes the change in the professionalization of the professor, raising the quality of the work in schools.